Организатор промышленности Украины (к 100-летиюсо дня рождения Н. А. Соболя) - Епифанов, Виталий Валерьевич; Писарская, Наталия Витальевна (НТУ "ХПИ", 2011)
Наведено основні етапи життя та творчої діяльності випускника Національного технічного університету «Харківський політехнічний інститут» М.О. Соболя, який пройшов шлях від техніка до директора потужного машинобудівного підприємства, видатного керівника промисловості України.

The main stages of life and creative activities of the National Technical University «Kharkiv polytechnical institute» graduation N.A. Sobol who has worked his way up from technician to director of the largest Machineruilding Enterprise and has become a monument leader of the industry of Ukraine are presented.
Keywords: Николай Александрович Соболь; выпускник НТУ "ХПИ"; завод транспортного машиностроения; высококвалифицированный специалист; руководитель производства